Characteristics and explanation of new artificial land uses on the example of Hungarian second-tier towns - Iváncsics, Vera (Journal of Environmental Geography, 2023)
The spatial growth of cities and the examination of the appearance of new artificial surfaces have been in the focus of several studies in the last decade. Attention was primarily focused on the metropolitan areas; however, the phenomenon can also be identified in smaller towns, which – at least, in Hungary – can hardly be explained by demographic trends. Urban growth, which is identified in the Carpathian Basin as well, is of concern from a sustainability point of view, so the monitoring and exploration of driving forces is of practical importance. Using the Corine Land Cover Database, the study analyses urban growth between 1990–2018 and looks for explanatory factors to understand the phenomenon. New artificial surfaces have appeared in the surroundings of cities or directly connected to morphological urban areas. Their morphological characteristics are presented on maps and in descriptive form. Those examples are interpreted for which the changes are not related to suburbanization trends or show unique characteristics in case studies. For example, in Sopron a large proportion of new residential areas are constantly appearing, thanks to its location on the border and the multi-centered metropolitan area of Vienna–Bratislava. The role of the ring road in the growth in Veszprém or the motorway construction in Nyíregyháza also determine spatial growth. Although the research approaches the issue of urban growth primarily from the point of view of morphology and land use, policy related conclusions can also be drawn from the results.